2014
DOI: 10.1176/appi.ps.201300243
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Housing: Assessing the Evidence

Abstract: Recovery housing appears to be an important component in the continuum of care for some individuals. However, replication of study findings with greater specificity and in more settings is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 15 publications
(25 reference statements)
2
37
0
Order By: Relevance
“…Research on recovery housing is promising, though there has been limited formal study of the model to date (Reif et al, 2014). Existing studies show positive outcomes including decreased substance use and incarceration and increased employment and income (Jason, Davis, Ferrari, & Anderson, 2007).…”
Section: What Is Recovery Housing?mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on recovery housing is promising, though there has been limited formal study of the model to date (Reif et al, 2014). Existing studies show positive outcomes including decreased substance use and incarceration and increased employment and income (Jason, Davis, Ferrari, & Anderson, 2007).…”
Section: What Is Recovery Housing?mentioning
confidence: 99%
“…Additionally, peer support enhances motivation and a sense of responsibility, as reported by the majority of residents and alumni (Jason, Aase, Mueller, & Ferrari, 2009). However, these positive findings are tempered by limitations in the research, including a lack of consistency in defining recovery housing program elements, small samples and single-site evaluations, and by small number of studies overall (Reif et al, 2014).…”
Section: What Is Recovery Housing?mentioning
confidence: 99%
“…Social support, such as that provided through 12-step program participation and social network support for sobriety, a key component of recovery housing, has been shown to directly affect recovery outcomes, including the probability of relapse (Jason et al, 2007;Polcin, Mericle, Howell, Sheridan, & Christensen, 2014;Bond, Kaskutas, & Weisner, 2003;Moos & Moos, 2006;Zywiak, Longabaugh, & Wirtz, 2002). However, due to the lack of a formal definition of recovery housing and a wide variety of models, evaluation is difficult and research gaps remain (Reif et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As such, we might expect fewer benefits from variably applied contingencies in heterogeneous community-based housing programs compared to the tightly controlled evidence-based abstinent-contingent housing programs as implemented in research studies (e.g., Milby et al, 1996; 2000; 2005; Tuten et al, 2012). Despite variabilities in program policies and contingencies, substance abusers in alcohol- and drug-free housing programs appear to benefit from participating in housing programs in terms of abstinence and psychosocial improvements (e.g., Jason et al, 2006; Jason et al, 2007b; Polcin, 2009; Polcin et al, 2010ab), and a recent meta-analysis of these programs (Reif et al, 2014) found moderate benefits of recovery housing relative to usual aftercare treatment (i.e., without housing) in terms of drug and alcohol use outcomes and some psychosocial domains.…”
Section: Introductionmentioning
confidence: 99%